2021
DOI: 10.1002/hed.26951
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adjuvant radiation to adjuvant chemoradiation in postsurgical p16+ oropharyngeal carcinoma patients with extranodal extension or positive margins

Abstract: Background Adjuvant guidelines in surgically resected p16+ oropharyngeal carcinoma (OPC) with positive surgical margins (PSM) or extranodal extension (ENE) are based on randomized controlled trials predating p16 status. It remains unclear if adjuvant chemotherapy is necessary in p16+ patients with these features. Methods The National Cancer Database was used to identify cases of nonmetastatic p16+ OPC diagnosed from 2010 to 2017. Patients treated with surgical resection followed by adjuvant radiation (aRT) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Results were promising: the primary endpoint of 2-year progression-free survival was 96.9% (90%CI, 91.9–100) in Arm A, 94.9% (90%CI, 91.3–98.6) in Arm B, 96.0% (90%CI, 92.8–99.3) in Arm C and 90.7% (90%CI, 86.2–95.4) in Arm D. These results are particularly impressive for patients with intermediate risk who were treated with reduced dose PORT and provide sound justification for a Phase III trial. In part confirmation of treatment deintensification for HPV-positive oropharyngeal cancer, a large-scale retrospective analysis of over 14 000 patients from the National Cancer Data Base reported that the addition of chemotherapy to PORT was not associated with an improvement in treatment outcomes for p16-positive oropharyngeal cancer patients with high-risk factors for recurrence ( 41 ). Nevertheless, any implementation of deintensification strategies in clinical practice should be approached with caution, since many randomized trials of deintensification for HPV-positive oropharyngeal cancer patients failed to show the non-inferiority of deintensification to the standard treatment strategy ( 42–44 ).…”
Section: Postoperative Treatment For the Patients With P16-positive O...mentioning
confidence: 99%
“…Results were promising: the primary endpoint of 2-year progression-free survival was 96.9% (90%CI, 91.9–100) in Arm A, 94.9% (90%CI, 91.3–98.6) in Arm B, 96.0% (90%CI, 92.8–99.3) in Arm C and 90.7% (90%CI, 86.2–95.4) in Arm D. These results are particularly impressive for patients with intermediate risk who were treated with reduced dose PORT and provide sound justification for a Phase III trial. In part confirmation of treatment deintensification for HPV-positive oropharyngeal cancer, a large-scale retrospective analysis of over 14 000 patients from the National Cancer Data Base reported that the addition of chemotherapy to PORT was not associated with an improvement in treatment outcomes for p16-positive oropharyngeal cancer patients with high-risk factors for recurrence ( 41 ). Nevertheless, any implementation of deintensification strategies in clinical practice should be approached with caution, since many randomized trials of deintensification for HPV-positive oropharyngeal cancer patients failed to show the non-inferiority of deintensification to the standard treatment strategy ( 42–44 ).…”
Section: Postoperative Treatment For the Patients With P16-positive O...mentioning
confidence: 99%